Asymmetric Aldol Reaction of Chloral Catalyzed by Diarylprolinol. Issue 11 (12th May 2015) - Hayashi, Yujiro; Watanabe, Shoya; Yasui, Yusuke; Umemiya, Shigenobu
Abstract The asymmetric cross‐aldol reaction of chloral hydrate with aldehyde pronucleophiles catalyzed by a trifluoromethyl‐substituted diarylprolinol was accomplished to afford γ‐trichloro‐β‐hydroxy aldehydes in good yields with excellent enantioselectivities. The resulting aldehyde products were converted into chiral α‐azido, α‐(4‐methyl)phenoxy, and α‐fluoro esters without a loss in the diastereo‐ or enantioselectivities.